Low Cost Synthesis and Characterization of Donor P3HT Polymer for Fabrication of Organic Solar Cell. Issue 1 (1st March 2022) - D S, Suresh; Vandana, M; Veeresh, S; Ganesh, H; Nagaraju, Y S; Vijeth, H; Basappa, M; Devendrappa, H
Abstract: Over the years, the conjugated polymers acts as electron donor material in the active layer of Organic solar cells (OSCs). By altering means of doping, prepare a composite with suitable materials from Poly (p-phenylene vinylene) PPV polymer toPM6 polymer which gives Power conversion efficiency (PCE) can vary from 2% to 15%. But these are expensive, complicated synthetic procedure and less availability. To overcome this, the conjugated polymer Poly (3-Hexyl Thiophene)(P3HT) synthesized through oxidative coupling of 3-HT monomer and Ferric chloride (FeCl3 ) as an oxidant which is low cost, available and very easy method of synthesis. We investigated synthesized P3HT material that shows the Fourier Transform Infrared(FTIR) peaks shows that intramolecular interactions from thiophene ring, alkyl chain and polymer chain, FESEM Images reveals morphology consists of condensed layers in micrometer dimensions and Cyclic voltammetry studies gives oxidation and reduction potentials to promote the higher ionization potential of the compound to use as donor material in OSCs.